2018
DOI: 10.1002/uog.18951
|View full text |Cite
|
Sign up to set email alerts
|

Differences in ultrasound features of papillations in unilocular‐solid adnexal cysts: a retrospective international multicenter study

Abstract: We have identified ultrasound features that can help to discriminate between benign and malignant unilocular-solid cysts with papillations but no other solid components. Our results need to be confirmed in prospective studies. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 31 publications
(44 reference statements)
1
19
0
1
Order By: Relevance
“…The finding that anechoic spaces in papillary projections was associated with malignancy is surprising in view of microcystic appearance of papillary projections being so common (38.6%) in the serous cystadenofibromas in our study. However, not all benign lesions in the study by Landolfo et al . were serous cystadenofibromas, which constituted only 29% of the benign lesions.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…The finding that anechoic spaces in papillary projections was associated with malignancy is surprising in view of microcystic appearance of papillary projections being so common (38.6%) in the serous cystadenofibromas in our study. However, not all benign lesions in the study by Landolfo et al . were serous cystadenofibromas, which constituted only 29% of the benign lesions.…”
Section: Discussionmentioning
confidence: 83%
“…A published retrospective analysis of 204 unilocular solid cysts with papillary projections, but no other solid components, showed that shadowing behind papillary projections was more often present in benign than in borderline or malignant cysts, while papillary projections with anechoic spaces were more often present in borderline or malignant cysts than in benign cysts, i.e. in 60% vs in 24%. The finding that anechoic spaces in papillary projections was associated with malignancy is surprising in view of microcystic appearance of papillary projections being so common (38.6%) in the serous cystadenofibromas in our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our series, only 47.8% of BOTs had papillary projections ≥ 3 mm on imaging; this discrepancy is most likely to be due to slight differences in the definition of papillae. One study, that of Landolfo et al 31 , provided an extensive sonographic evaluation of papillae in unilocular-solid adnexal cysts, describing '11 ultrasound features of papillations and the cyst wall', including the number of papillae, their height in millimeters, their contour, the presence of intrapapillary blood flow, the percent of papillary dissemination, the papillary angle relative to the inner cyst wall and the echogenicity of the projections, and describing the acoustic shadows cast by the papillae. They highlighted that there were 'anechoic spaces present in at least one papilla' in 62% of BOTs and 58% of malignant entities.…”
Section: Discussionmentioning
confidence: 99%